Permeability of Polyamide6 Nanofiber for Air Filtrations (Journal of University of Babylon for Engineering Sciences, 2017)
Polyamide6(PA6) nanofibers are prepared in this study for air filter applications by electrospinning technique. The electrospun solution (21% PA6 concentration) is prepared by dissolving PA6 powder in formic acid. Permeability, filter efficiency, thickness of filters and pores size are measured to characterize the air filter membranes. Results prove that the efficiency of filter is ranging between (93-95%), AFM test shows that all samples have a pore size between (71-101 nm), that is corresponding with(ASHRAE Standard 52.1 and 52.2) which makes the air filters in this search working at  hospital care, smoke lounge and general surgery applications.